The European Medicines Agency Review of Carfilzomib for the Treatment of Adult Patients with Multiple Myeloma Who Have Received at Least One Prior Therapy. (21st September 2017) - Tzogani, Kyriaki; Camarero Jiménez, Jorge; Garcia, Isabel; Sancho‐López, Arantxa; Martin, Marc; Moreau, Alexandre; Demolis, Pierre; Salmonson, Tomas; Bergh, Jonas; Laane, Edward; Ludwig, Heinz; Gisselbrecht, Christian; et al.
Abstract: On November 19, 2015, a marketing authorization valid through the European Union was issued for carfilzomib in combination with lenalidomide and dexamethasone for the treatment of adult patients with multiple myeloma (MM) who have received at least one prior therapy. In a phase III trial in patients with relapsed MM, median progression‐free survival (PFS) for patients treated with carfilzomib in combination with lenalidomide and dexamethasone (CRd) was 26.3 months versus 17.6 months for those receiving lenalidomide and dexamethasone alone (hazard ratio = 0.69; 95% confidence interval, 0.57–0.83; one‐sided log‐rank p value < .0001). The most frequently observed toxicity (grade ≥3, treatment arm vs. control arm) in the phase III trial included neutropenia (29.6% vs. 26.5%), anemia (17.9% vs. 17.7%), thrombocytopenia (16.8% vs. 12.3%), pneumonia (12.5% vs. 10.5%), fatigue (7.7% vs. 6.4%), hypertension (4.6% vs. 2.1%), diarrhea (3.8% vs. 4.1%), and respiratory tract infection (4.1% vs. 2.1%). The objective of this article is to summarize the scientific review of the application leading to regulatory approval in the European Union. The scientific review concluded that the gain in PFS of 8.7 months observed with the combination of CRd was considered clinically meaningful and was supported by a clear trend in overall survival benefit, although the data were not mature. The delay in disease progression appeared superior to available alternatives in the setting of relapsed MM at the time of the marketing authorization of carfilzomib. Therefore, given the overall accepted safety profile, which was considered manageable in the current context, the benefit risk for CRd was considered positive. Abstract : This article summarizes the scientific review of the application leading to regulatory approval of carfilzomib in combination with lenalidomide and dexamethasone in the European Union.